FOWLER'S SYNDROME OF URINARY RETENTION: A RETROSPECTIVE STUDY OF CO-MORBIDITY. Issue 9 (13th August 2015) - Hoeritzauer, Ingrid; Stone, Jon; Fowler, Clare; Elneil, Sohier; Carson, Alan; Panicker, Jalesh
Abstract : Objective: Fowler's syndrome describes chronic urinary retention in young women characterised by a primary failure of urethral sphincter relaxation and unique urethral sphincter EMG findings in the absence of any structural pathology. We aimed to systematically study the frequency of pain, psychological or functional disorders in patients with Fowler's syndrome. Method: We carried out a retrospective chart review of patients with a diagnosis of Fowler's syndrome attending the Uro-Neurology centre at the National Hospital for Neurology and Neurosurgery between 2009–2013 looking at triggering events, physical and psychological comorbidities. Results: Of 62 patients with clinical and electromyographic diagnosis of Fowler's syndrome, 31 (50%) had unexplained chronic pain syndromes, 12 (19%) of these were taking opiates. 15 (24%) had "functional" neurological symptoms. Abdominopelvic surgery with general anaesthesia was the leading trigger (n=21, 35%). Conclusion: We found high levels of co-morbidity with patients having some form of pain (50%), a probable functional disorder (24%) or psychological symptoms (31%). There are several potential explanations for this association including the effect of developing an apparently unexplained distressing condition, confounding effect of opiate use or referral bias. The findings suggest a need for prospective systematic study of comorbidity for this disabling condition.